Anion exchange in inorganic perovskite nanocrystal polymer composites. Issue 42 (6th September 2018) - Sygletou, Maria; Kyriazi, Maria-Eleni; Kanaras, Antonios G.; Stratakis, Emmanuel
Abstract : We demonstrate a facile, low-cost and room-temperature method of anion exchange in cesium lead bromide nanocrystals (CsPbBr3 NCs), embedded into a polymer matrix. Abstract : We demonstrate a facile, low-cost and room-temperature method of anion exchange in cesium lead bromide nanocrystals (CsPbBr3 NCs), embedded into a polymer matrix. The anion exchange occurs upon exposure of the solid CsPbBr3 NCs/PDMS nanocomposite to a controlled anion precursor gas atmosphere. The rate and extent of the anion exchange reaction can be controlled via the variation of either the exposure time or the relative concentration of the anion precursor gas. Post-synthesis chemical transformation of perovskite nanocrystal–polymer composites is not readily achievable using conventional methods of anion exchange, which renders the gas-assisted strategy extremely useful. We envisage that this work will enable the development of solid-state perovskite NC optoelectronic devices.